Time-resolved Raman spectroscopy of hexafluorobenzene (C6F6) under laser-driven shock compression. (March 2021) - Mohan, Ashutosh; Chaurasia, S.; Rao, Usha; Pasley, John
Highlights: Time resolved Raman Spectroscopy of the hexafluorobenzene under extreme conditions at molecular level has been done. The phase transitions under high pressure has been studied. One Dimensional hydrodynamic simulation is performed to validate the experimental data. Laser driven flyer is developed for the shock compression in the hexafluorobenzene sample. Abstract: Hexafluorobenzene is used as a cooling fluid in nuclear reactors, in production of pharmaceutical compounds and in prognostic biomarkers. It is useful to understand the dynamics of Hexafluorobenzene under extreme conditions. For the first time, we have performed Time-Resolved Raman Spectroscopy of laser shocked Hexafluorobenzene using a pump-probe technique to study the effect of high pressure at the molecular level and possible phase transitions. A 2 J / 8 ns Nd: YAG laser system is used for generating shock pressures of up to 4.5 GPa in the sample in a confined geometry. Three prominent modes at 370 cm −1 (e1g fundamental mode or ν10 ), 445 cm −1 (e2g fundamental mode or ν6 ) and 560 cm −1 (a1g fundamental mode or ν1 ) exhibit blue shift with scaling factors of 370 + 0.88 P(GPa), 445 +1.22P(GPa) and 560 +1.93P(GPa) respectively. A liquid→Phase-II phase transition is observed at a pressure of 0.9 GPa which is very close to the 0.8 GPa pressure at which a phase transition has been reported to occur under static compression. The shock velocity in Hexafluorobenzene at a laser energy of 300 mJ and 500 mJ is calculated by measuring the intensity ratio of Raman modes emerging from the shocked region to that of the whole sample. To validate the experimental results, 1-D radiation hydrodynamics simulations are also performed. Experimentally obtained shock velocities, at a laser intensity of 1.47 GW/cm 2 (300 mJ) and 2.46 GW/cm 2 (500 mJ), are 2.54 km/s and 3.65 km/s respectively which are in close agreement with simulation results of 2.98 km/s and 3.84 km/s respectively. Gruneisen parameters corresponding to the three modes are also calculated which are 0.00950 ± 0.0140 (ν10 mode), 0.0433 ± 0.0060 (ν6 mode), and 0.0561 ± 0.0044 (ν1 mode) respectively.